An unusual case of Pasteurella multocida bacteremic meningitis - Nikolaos Katechakis; Sofia Maraki; Irini Dramitinou; Eleni Marolachaki; Christina Koutla; Eleni Ioannidou (Elsevier, 2019)
Pasteurella multocida is a rare cause of bacterial meningitis, more frequently affecting humans at the extremes of age. We report a case of meningitis and bacteremia caused by P. multocida in a 67-year-old diabetic woman who was living with 10 cats. She didn't have any animal bites or scratches, but she reported kissing the pets in the mouth. The outcome was favorable following antimicrobial treatment. Although rarely encountered, P. multocida should be considered as a possible cause of meningitis, particularly when Gram-negative coccobacilli are revealed in the cerebrospinal fluid and a history of recent animal contact is present. Keywords: Pasteurella multocida, Meningitis, Bacteremia, Cats, Kissing